2020
DOI: 10.3390/electronics9091514
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Phishing Detection Model Based on Character Level Convolutional Neural Network from URL

Abstract: Phishing is the easiest way to use cybercrime with the aim of enticing people to give accurate information such as account IDs, bank details, and passwords. This type of cyberattack is usually triggered by emails, instant messages, or phone calls. The existing anti-phishing techniques are mainly based on source code features, which require to scrape the content of web pages, and on third-party services which retard the classification process of phishing URLs. Although the machine learning techniques have latel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…Similarly, the authors of [24,28,29,32] described the optimization process, but only on certain parameters, for example, the number of convolutional layers, number of kernels, and kernel size. Additionally, in terms of performance metrics, it was observed that accuracy, precision, recall, and F1-score were the most common measures [7,24,28,[30][31][32]34,35,37,38]. Other evaluation metrics were training time, detection time, GPU memory requirement, etc.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the authors of [24,28,29,32] described the optimization process, but only on certain parameters, for example, the number of convolutional layers, number of kernels, and kernel size. Additionally, in terms of performance metrics, it was observed that accuracy, precision, recall, and F1-score were the most common measures [7,24,28,[30][31][32]34,35,37,38]. Other evaluation metrics were training time, detection time, GPU memory requirement, etc.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…CNN was used as a single classifier in numerous research to distinguish between phishing and legitimate websites [7,8,20,[24][25][26][27][28]. It can also be used in combination with other DL techniques to form an ensemble model and to improve phishing detection accuracy [10,11,[29][30][31][32][33][34][35][36].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of this study indicated that the value of true positive was higher rather than the false positive rate. In other study [ 10 ], authors proposed a Convolutional Neural Network (CNN) to detect a phishing URL. In this study, researchers employed a sequential pattern to capture the URL information.…”
Section: Research Background and Related Workmentioning
confidence: 99%
“…There is a significant chance of exploitation of user information. For these reasons, phishing in modern society is highly urgent, challenging, and overly critical [ 9 , 10 ]. There have been several recent studies against phishing based on the characteristics of a domain, such as website URLs, website content, incorporating both the website URLs and content, the source code of the website and the screenshot of the website [ 11 ].…”
Section: Introductionmentioning
confidence: 99%